ҲƏЗИРГИ ҚАРАҚАЛПАҚ ПОВЕСТЬЛЕРИНДЕ ҚАҲАРМАН ОБРАЗЫ МƏСЕЛЕСИ - Сагидуллаева, З.Б. (FAN va JAMIYAT, 2016)
The article is devoted to the study of an actual problem of tendencies of modern Karakalpak stories development on the example of M. Nyzanov's work "A dream at deaths door". The author describes the criteria promoting disclosure by the writer of an image of the main hero of the work. The writer's lock for the devices of the plot-compositional structure of the work is analyzed in close connection with skill of disclosure of an image of the main character of the work. The attention is paid to the details which have formed the conflict basis.